The experiences of people with Alzheimer's dementia and their caregivers in acquiring and using a mobility aid: a qualitative study. Issue 23 (6th November 2021) - Hunter, Susan W.; Meyer, Claudia; Divine, Alison; Hill, Keith D.; Johnson, Andrew; Wittich, Walter; Holmes, Jeff
Abstract: Purpose: Cognitive deficits and gait and balance problems are progressive in people with Alzheimer's dementia. Yet, mobility aids are associated with an increased falls risk in people with dementia. Our objectives were to identify the perceptions of people living with mild-to-moderate Alzheimer's dementia, and their caregivers, on the use of mobility aids. Methods: A qualitative study using semi-structured, face-to-face interviews was conducted. Community-dwelling older adults with dementia attending a day hospital program were recruited. Thematic analysis was conducted and the text was coded into broad themes aligned with the research questions. The coded text was examined for patterns and similarities, and grouped to form inductive themes. Results: Twenty-four people (12 living with dementia and their 12 caregivers) participated. Five themes were identified: (1) acknowledgement of need ; (2) protecting a sense of self ; (3) caregiver oversight and relief of burden ; (4) healthcare professional involvement; (5) environment and design of aids. Conclusions: The findings suggest that people with Alzheimer's dementia and their caregivers regard mobility aid use as increasing independence. There is a role for healthcare professionals to be involved in the prescription, provision and training for use of mobility aids among people living with dementia to ensure uptake and safety. IMPLICATIONS FOR REHABILITATION: Mobility aid use is regarded as increasing independence by people with Alzheimer's disease and their caregivers. Falls risk associated with mobility aid use was not well known and caregivers perceived mobility aids as a means to reduce falls. Most people do not see a healthcare professional when they acquire a mobility aid and there is a role for healthcare professionals to be involved in the prescription, provision and training of people living with dementia in the use of mobility aids in order to increase the uptake of aids and their safe use.